Pregunta
upstudy study bank question image url

1 Solve for \( x \) and \( y \) in the fol a \( 3 y+x=2 \) \( y^{2}+x=x y+y \)

Ask by Lee Hobbs. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are: - \( x = -1 \) and \( y = 1 \) - \( x = 0.5 \) and \( y = 0.5 \)

Solución

We are given the system of equations:   1) 3y + x = 2   2) y² + x = xy + y Step 1. Solve the first equation for x:   x = 2 − 3y Step 2. Substitute x = 2 − 3y into the second equation:   y² + (2 − 3y) = y(2 − 3y) + y Step 3. Expand the right-hand side:   y(2 − 3y) + y = 2y − 3y² + y = 3y − 3y² So the equation becomes:   y² + 2 − 3y = 3y − 3y² Step 4. Bring all terms to one side to set the equation to zero:   y² + 2 − 3y − 3y + 3y² = 0 Combine like terms:   (1y² + 3y²) − 6y + 2 = 0   4y² − 6y + 2 = 0 Step 5. Simplify the quadratic equation by dividing the entire equation by 2:   2y² − 3y + 1 = 0 Step 6. Solve the quadratic equation 2y² − 3y + 1 = 0 using the quadratic formula:   y = [−(−3) ± √((−3)² − 4·2·1)] / (2·2)   y = [3 ± √(9 − 8)] / 4   y = [3 ± 1] / 4 Thus, we have two solutions:   • For the positive square root: y = (3 + 1) / 4 = 4/4 = 1   • For the negative square root: y = (3 − 1) / 4 = 2/4 = 1/2 Step 7. Now, use the expression for x (x = 2 − 3y) to find the corresponding x values.   • If y = 1: x = 2 − 3(1) = 2 − 3 = −1   • If y = 1/2: x = 2 − 3(1/2) = 2 − 1.5 = 0.5 Therefore, the solutions to the system are:   (x, y) = (−1, 1) and (x, y) = (0.5, 1/2)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve this system of equations, we start with the first equation: 1. From \( 3y + x = 2 \), we can express \( x \) in terms of \( y \): \[ x = 2 - 3y \] Now, we substitute \( x \) in the second equation: 2. The second equation is \( y^2 + x = xy + y \). Replacing \( x \) with \( 2 - 3y \): \[ y^2 + (2 - 3y) = (2 - 3y)y + y \] 3. Simplifying both sides, we have: \[ y^2 + 2 - 3y = 2y - 3y^2 + y \] \[ y^2 + 2 - 3y = -3y^2 + 3y \] 4. Now, moving all terms to one side: \[ y^2 + 3y^2 - 3y - 3y + 2 = 0 \] \[ 4y^2 - 6y + 2 = 0 \] 5. Dividing everything by 2: \[ 2y^2 - 3y + 1 = 0 \] 6. Now, we can use the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ y = \frac{3 \pm \sqrt{(-3)^2 - 4 \cdot 2 \cdot 1}}{2 \cdot 2} \] \[ y = \frac{3 \pm \sqrt{9 - 8}}{4} \] \[ y = \frac{3 \pm 1}{4} \] Thus, \( y = 1 \) or \( y = \frac{1}{2} \). 7. Now substituting these values back to find \( x \): - For \( y = 1 \): \[ x = 2 - 3(1) = -1 \] So one solution is \( (x, y) = (-1, 1) \). - For \( y = \frac{1}{2} \): \[ x = 2 - 3\left(\frac{1}{2}\right) = 2 - \frac{3}{2} = \frac{1}{2} \] Hence, another solution is \( (x, y) = \left(\frac{1}{2}, \frac{1}{2}\right) \). The final solutions are: 1. \( (x, y) = (-1, 1) \) 2. \( (x, y) = \left(\frac{1}{2}, \frac{1}{2}\right) \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad